Plasmid-based and genome-based expression of recombinant T1 lipase in sucrose-utilizing E. coli strain W - Yusof, Siti Hajar; Leow, Adam Thean Chor; Rahman, Raja Noor Zaliha Raja Abd; Ngalimat, Mohamad Syazwan; Lim, Si Jie; Sabri, Suriana (University of Malaya, 2024)
Given its thermoalkaliphilic properties, T1 lipase holds significant potential for diverse industrial applications. However, traditional expression methods in Escherichia coli, specifically the plasmid-based system, present challenges of exerting metabolic burden on host cells and elevated costs due to antibiotic usage. This study addresses these issues by pioneering the expression of recombinant T1 lipase in a sucrose-utilizing E. coli strain W, using molasses as an economical carbon source. The gene cassette (KIKO plasmid), containing the T1 lipase gene regulated by tac and trc promoters, was integrated into the E. coli genome via the λ Red recombinase system. T1 lipase was optimally expressed in shake flasks at 16°C and a 3% molasses concentration in M9 medium with 0.8 mM IPTG as inducer, yielding 0.44 U/mL activity in the genome-based system compared to 0.94 U/mL in the plasmid-based system. This study not only underscores the potential of employing sucrose-utilizing E. coli strain for industrial recombinant protein production but also highlights the need for further optimization of genome-based expression systems. It offers an alternative to reduce costs and enhance sustainability in the stable production of industrially relevant enzymes like T1 lipase, without the need for antibiotic supplementation, and has broader implications for leveraging inexpensive carbon sources like molasses in biotechnological applications.